Інституціональна платформа забезпечення інноваційного розвитку підприємств агропромислового виробництва - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Вініченко, І. І. (My University, 2020)
UK: У статті розглядається інституційна платформа для забезпечення інноваційного розвитку підприємств агропромислового виробництва України. Побудована ефективна функціональна система, яка на основі кількісних та якісних критеріїв визначає масштаби та ефективність діяльності підприємств, забезпечує можливості відтворення ресурсного потенціалу агропромислового виробництва. EN: The article deals with the institutional platform for insuring of the innovative development of the enterprises of agro-industrial production of Ukraine. An effective functional system has been built which, based on the quantitative and qualitative criteria, determines the scale and effectiveness activity of enterprises, provides opportunities to reproduce the resource potential of the agro-industrial production. The set of processes of relevant implication “resources - structure - efficiency - development of the system” was singled out in order to improve the qualitative and quantitative properties of the production cycle as a creation of efficiency. The criterion of “optimal maximum profit”, which meets the requirements of a clear economic interpretation of the performance indicators, provides an increase in the value of cash flow to reduce the dependence of the entities of inter-economic relations on the slowdown in the inno-vative development of the production cycle. It is proved that the integration of the enterprises of agro-industrial production with a long continuous cycle has specified functional changes in their efficiency. We have grouped the entities of inter-economic relations by the level of production cost and profit-ability of the sold products, which ensure the effective process of functioning of the enterprises of the agro-industrial production. The parameters of resource load on indicators of innovative development of the production of enterprises of poultry production in the average for one region of Ukraine are determined. Alternative business projects for the production of poultry products are proposed while changing the cash flow discount rate.
Institutional platform for ensuring innovative development of the enterprises of the agro-industrial production
Keywords: інституційна платформа; інноваційний розвиток; агропромислове виробництво; виробничий цикл; витрати; рентабельність; підприємство; institutional platform; innovative development; agro-industrial production; production cycle; costs; profitability; enterprise